TINDAK TUTUR ILOKUSI DIREKTIF DALAM INTERAKSI PEMBELAJARAN DI SMP EVANS INDONESIA KOTA BANGUN - Yanuarika Wulan Rahmadhani (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The purpose of this study is to gain a deep understanding of directive illocution speech in the learning interaction of Evans Indonesia Junior High School Kota Bangun. This research was conducted during May 2024 in grades VII and VIII of Evans Indonesia Junior High School Kota Bangun. This research is focused on directive illocution speech, types of directive illocution speech, and functions of directive illocution speech. This study uses a qualitative research method with a communication ethnographic study that examines directive illocution speech in actual situations. Research data was collected by listening, interviewing, observing, and recording methods. The data were then grouped into speech pairs with units of communicative situation analysis, communicative events, and communicative actions. The results of this study show that there are five types and functions of directive illocution speech actions found in the learning interaction of SMP Evans Indonesia Kota Bangun namely the categories of commanding, requesting, forbidding, warning, and recommending.